LOWER CORRELATION BETWEEN BICEPS FEMORIS CONTRACTION TIME AND MAXIMAL RUNNING SPEED IN CHILDREN THAN IN ADULTS: A LONGITUDINAL STUDY IN 9- TO 14-YEAR OLD CHILDREN - Jernej Završnik; Rado Pišot; Tadeja Volmut; Katja Koren; Helena Blažun Vošner; Peter Kokol; Janez Vošner; Boštjan Šimunič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2016)
Biceps femoris is a major propulsor muscle in sprinting and its contraction time negatively correlates to the running speeds of adults. Our aim was to compare age and gender- related correlations between vastus lateralis and biceps femoris contraction times and running speeds during a longitudinal study of 9- to 14-year old children. On a yearly basis we conducted vastus lateralis and biceps femoris tensiomyographic measurements of muscle contraction time and maximal running speeds measured during 7 meter sprints with flying starts using photocells in 107 children (53 boys). Vastus lateralis contraction time was not correlated with the running speed. However, biceps femoris contraction time was negatively correlated with the running speed only in boys after the age of 12.9 years (Pearson r ranges from -0.391 to -0.426; < 0.002). It was concluded that biceps femoris contraction time is far less correlated with running speed than in adult athletes (Pearson r = -0.60); however, the correlation is gender and age- specific. It seems that the knee flexor and hip extensor, biceps femoris, is not as yet the major determinant of running speed in 9- to 14-year old children at that age.